Educação escolar e saúde indígena: uma análise comparativa das políticas nos níveis federal e local - Craveiro, Silvia da Silva (2004)
This work presents a study about the school education and health policies for indigenous people in Brazil. The main objective is to verify the presence of the tendencies of modification observed in the social policies in the country, from the decades of 1980 and 1990: decentralization of the policies for sub national levels; creation of institutional mechanisms for the participation of the civil society in the management of public policies; establishment of partnerships with private institutions; alteration in the content of the policies and enlargement of the reach of the policies. The study was carried out from a comparative analysis of the two policies in the federal and in the local level of government. The analysis in the local level was carried out from a case study of the Parque Indígena do Xingu (Indigenous Park of the Xingu). It sought be verified, in the path of the politics, the influence of the factors related to the trials of redemocratization and State Reform, of the own dynamics of the health and education areas, of the state agenda for indigenous issues. From the analysis, we verify, in the federal level, an improvement in the legislation in both areas, compared with the existing beginnings before of the Federal Constitution of 1988. In what refers to the legislation, the indigenous school education presents-itself more consolidated when compared to the health that still presents some questions. In the Indigenous Park of the Xingu we perceive an inflection in the two policies, from the decade of 1990, that pass seek it a growing one indigenous protagonism and to enhance of an intercultural approach. In the Xingu these advancements were turned out, especially, of the initiative of the native communities of the region, in co-owner with the Universidade Federal de São Paulo, in the area of the health, and with the Instituto Socioambiental, in the area of the education, and with resources, at the beginning, of international foundations.